Preparing for Digital Disruption - Schrijvers, Erik; Prins, Corien; Passchier, Reijer (Research for Policy, Studies by the Netherlands Council for Government Policy, 2021)
This open access book offers an analysis of why preparations for digital disruption should become a stated goal of security policy and policies that aim to safeguard the continuity of critical infrastructure. The increasing use of digital technology implies new and significant vulnerabilities for our society. However, it is striking that almost all cyber-security measures taken by governments, international bodies and other major players are aimed at preventing incidents. But there is no such thing as total digital security. Whether inside or outside the digital domain, incidents can and will occur and may lead to disruption. While a raft of provisions, crisis contingency plans and legal regulations are in place to deal with the possibility of incidents in the 'real world', no equivalence exists for the digital domain and digital disruption. Hence, this book uniquely discusses several specific policy measures government and businesses should take in order to be better prepared todeal with a digital disruption and prevent further escalation.